Work-Family Stressors and Work-Family Satisfaction: Effect of Sense of Coherence at a Metropolitan Municipality - Ethel N. Abe; Isaac I. Abe; Ziska Fields; Ganiyu O. Idris (Journal of Economics and Behavioral Studies, 2018)
This article contributes to emergent research by examining the linkage between work–family stressors and their effect on work-family satisfaction (WFS) at a metropolitan municipality in South Africa. Extant literature on stress has either not adequately examined the linkage between domain specific stressors and domain specific satisfaction or have suggested models with direct connections. The present study suggests a mediating model and assesses the mediation. Specifically, it claims that sense of coherence (SOC) plays a mediating part in the in the work and family stressors - WFS relationship. This mixed methods research applied a variance-based structural equation modelling (Partial Least Squares) to a sample of 307 professional level employees at a metropolitan municipality in South Africa. The finding supports the importance of SOC and its influence on WFS. Additionally, mediation hypotheses theorise how SOC plays a critical mediating influence in the work-family stressor-WFS relationship. Data analysis suggest that (a) work stressors and WFS interrelated in a manner that SOC fully mediated the effect of work stressors on WFS (b) SOC partially mediated the relationship between family stressors and WFS. The findings have both theoretical and practical implications.